Heat Treatment and Ventilation Optimization in a Deep Mine - Xingxin Nie; Xiaobin Wei; Xiaochen Li; Caiwu Lu (Advances in Civil Engineering)
In order to address the issue of high temperatures and thermal damages in deep mines, the factors causing downhole heat damage at high temperatures were analyzed, the mine ventilation system was optimized and rebuilt, and a cooling system was established. The proposed cooling system uses mine water as the cooling source, and its features are based on the analysis of traditional cooling systems. The current ventilation system in the 1118 m deep pit of the Jinqu Gold Mine was evaluated, and the ventilation network, ventilation equipment, and ventilation structures near the underground working face were optimized. The low-temperature mine water stored in the middle section of the mine at 640 m depth was used as the cooling source, and a cooling system was established near the 440 m deep middle return well to alleviate the high-temperature and high-humidity conditions of the 280 m deep middle-western area. The results show that the effective air volume in the west wing at 280 m was 3.0 m3/s, the operating ambient temperature was 27.6°C, the relative humidity was reduced to 76%, and the temperature was reduced by 5-6°C after the optimization of the system.